Optical fibre sensors for novel medical devices during anaesthesia - Hernandez Ledezma, Francisco Ulises (2018)
This research focuses on the development of optical fibre sensors that can be applied during critical care. The sensors developed are: (i) an optical fibre humidity sensor based on the deposition of a hygroscopic film onto the distal tip of the fibre and forming a Fabry-Pêrot cavity; (ii) chemical functionalization of U-shaped fibres and Long Period Gratings (LPGs). Fibre Bragg Gratings (FBGs) are only used for temperature monitoring in this work. The current trends in a new generation of humidity sensors suggest that electronic-based technologies could be soon replaced by photonic sensors due to better response times. Optical fibre technology has been considered as a promising platform for providing engineering solutions to unmet clinical needs. For example, anaesthetized patients are transferred from the induction room to the MRI room and taken back, with the need for continuous monitoring of vital signs such as respiration, but some technologies lack compatibility with MRI fields. In the operating room, patients are under anaesthesia, intubated and mechanically ventilated, but some under-humidification or over-humidification of the ventilation air causes secondary effects. Anaesthesiologists rely on total intravenous anaesthesia (TIVA) and monitoring of vital signs as indicators of unconsciousness; current investigations have shown that there is a need to measure the concentration of propofol in real time directly from the blood or breath of patients. Similarly, patients in the intensive care unit (ICU) after surgery require continuous monitoring of diverse biochemical parameters. In this research, the application of optical fibre sensors is demonstrated as an engineering solution for some of these clinical challenges. The simultaneous measurement of humidity and temperature with an optical fibre sensor, a biosensor for propofol detection and another for protein detection were fabricated and demonstrated in this work. The sensitivity, response time and hysteresis of a novel optical fibre humidity sensor has been investigated over a humidity range of 5% Relative Humidity (RH) to 95% RH using a controlled bench-top set-up. The optical fibre humidity sensor proposed has a very simple and low cost porous structured sensing element obtained with poly(allylamine hydrochloride) (PAH) and silica (SiO2) using the layer-by-layer (LbL) fabrication method. The fast response of the sensor (1.13 ± 0.3 s) enabled changes in humidity in individual breaths to be resolved. After calibration, the performance of the sensor was evaluated in the breathing circuit of a mechanical ventilator and respiratory equipment where its faster response allowed monitoring of breath to breath humidity levels during different modes of ventilation. It also has the capability to provide absolute humidity (AH) measurements when an FBG is included for simultaneous temperature measurements. An LPG sensor anchored with SiO2 core and gold (Au) shell nanoparticles has been investigated as a biosensing platform for protein detection. The well-known protein interaction between biotin and streptavidin (SV) was used as a proof of concept. The proposed sensor presented Langmuir adsorption to SV concentrations with a limit of detection (LoD) down to 15.13 nM and a lowest detected concentration of 2.5 nM. In addition, U-shaped fibres and LPGs functionalized with host-guest imprinted TiO2 thin films were used to test propofol detection in aqueous solutions. These sensors also presented Langmuir adsorption in the mili-molar range in aqueous solutions and a lowest detected concentration of 0.65 uM. Detection limits of propofol were improved with the addition of mesoporous silica nanoparticles (MSNs) and inorganic molecular imprinting to allow detection down to 99 nM in aqueous solution and 30 ppb in gaseous phase. In conclusion, this research has successfully demonstrated the use of novel optical fibre sensors in laboratory and real conditions through embedding the developed sensors in critical care equipment usually used during anaesthesia.